2008
DOI: 10.1158/0008-5472.can-07-5590
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Mechanisms Mediating Tumor-Specific Changes in Gene Expression in Human Liver Tumors

Abstract: There is widespread interest in efficient characterization of differences between tumor and normal samples. Here, we show an effective methodology for genome-scale characterization of tumors. Using matched normal and tumor samples from liver cancer patients, as well as non-cancer-related normal liver tissue, we first determined changes in gene expression as monitored on RNA expression arrays. We identified several hundred mRNAs that were consistently changed in the tumor samples. To characterize the mechanisms… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 32 publications
3
34
1
Order By: Relevance
“…These results confirm identity relationships of different fibroblasts previously shown using RNA expression analyses (Rinn et al 2006). We also found that mES cells clustered close to the Ntera2 embryonal cancer cell line, which we have previously shown to have a similar chromatin structure as ES cells (Squazzo et al 2006), and that, as expected, the liver tissues were close to each other regardless of normal or tumor state (Acevedo et al 2008). Comparison of the gene ontology categories of the POLR2A-bound sets of LEGs (Fig.…”
Section: Distinct Classes Of Genes Are Repressed By Certain Mechanismssupporting
confidence: 90%
See 2 more Smart Citations
“…These results confirm identity relationships of different fibroblasts previously shown using RNA expression analyses (Rinn et al 2006). We also found that mES cells clustered close to the Ntera2 embryonal cancer cell line, which we have previously shown to have a similar chromatin structure as ES cells (Squazzo et al 2006), and that, as expected, the liver tissues were close to each other regardless of normal or tumor state (Acevedo et al 2008). Comparison of the gene ontology categories of the POLR2A-bound sets of LEGs (Fig.…”
Section: Distinct Classes Of Genes Are Repressed By Certain Mechanismssupporting
confidence: 90%
“…After confirmation that the ChIP assay was successful, amplicons were prepared and tested using the same positive and negative control primer sets (see Supplemental Fig. S4; see also Acevedo et al 2007Acevedo et al , 2008O'Geen et al 2007). After demonstrating that the amplicons were accurate representations of the starting ChIP samples, they were labeled and hybridized to mouse or human promoter arrays (see Supplemental Table S1 for a description of the type of promoter array used for each sample).…”
Section: Identification Of Genes Repressed By Five Different Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to snoRNAs, the upregulation of R2TP has also been reported in various cancer cells as shown in Table 2. For example, in human hepatocellular carcinoma (HCC), the mRNA and/or protein levels of RuvBL1/ pontin and RuvBL2/reptin are increased as compared to non-tumor liver (55)(56)(57)(58)(59)(60). Also, it has been shown that RuvBL1/pontin is overexpressed in breast, colon, and colorectal cancers (61)(62)(63)(64) and RuvBL2/reptin is overexpressed in breast, colon, gastric, and renal cell cancers (62,(65)(66)(67).…”
Section: Potential Role Of R2tp In Tumorigenesis Through Snornp Pathwaymentioning
confidence: 99%
“…In fact, very few polycomb profiles in particular and histone modification profiles in general are currently available from normal human primary tissues. 6 Therefore, in order to properly establish if polycomb-premarking of cancer DNA hypermethylation events is limited to ES cells or if it could also arise in differentiated precursors, polycomb/H3K27me3 profiles from normal tissues would be needed.…”
Section: © 2 0 0 9 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%